Consequences of intra-canopy and top LED lighting for uniformity of light distribution in a tomato crop - Schipper, R.; van der Meer, M.; de Visser, P.H.B.; Heuvelink, E.; Marcelis, L.F.M. (Frontiers in Plant Science, 2023)
In the past decade, the potential of Intra-canopy light emitting diode (LED) lighting to enhance or modify crop growth and yield has been explored in greenhouse cultivation. Changes in spatial heterogeneity of light absorption that come with the introduction of Intra-canopy lighting have not been thoroughly explored. We calibrated and validated an existing functional structural plant model (FSPM), which combines plant morphology with a ray tracing model to estimate light absorption at leaflet level. This FSPM was used to visualize the light environment in a tomato crop illuminated with Intra-canopy lighting, top lighting or a combination of both. Model validation of light absorption of individual leaves showed a good fit (R2 = 0.93) between measured and modelled light absorption of the canopy. Canopy light distribution was then quantified and visualized in three voxel directions by means of average absorbed photosynthetic photon flux density (PPFD) and coefficient of variation (CV) within that voxel. Simulations showed that the variation coefficient within horizontal direction was higher for Intra-canopy lighting than top lighting (CV=48% versus CV= 43%), while the combination of Intra-canopy lighting and top lighting yielded the lowest CV (37%). Combined Intra-canopy and top lighting (50/50%) had in all directions a more uniform light absorption than Intra-canopy or top lighting alone. The variation was minimal when the ratio of PPFD from Intra-canopy to top lighting was about 1, and increased when this ratio increased or decreased. Intra-canopy lighting resulted in 8% higher total light absorption than top lighting, while combining 50% Intra-canopy lighting with 50% top lighting, increased light absorption by 4%. Variation in light distribution was further reduced when the Intra-canopy LEDs were distributed over strings at four instead of of two heights. When positioning LED lamps to illuminate a canopy both total light absorption and light distribution have to be considered.